2001
DOI: 10.1207/s15326942dn1903_3
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning as a Predictor of Children's Mathematics Ability: Inhibition, Switching, and Working Memory

Abstract: Children's mathematical skills were considered in relation to executive functions. Using multiple measures--including the Wisconsin Card Sorting Task (WCST), dual-task performance, Stroop task, and counting span-it was found that mathematical ability was significantly correlated with all measures of executive functioning, with the exception of dual-task performance. Furthermore, regression analyses revealed that each executive function measure predicted unique variance in mathematics ability. These results are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

80
1,040
11
74

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,243 publications
(1,205 citation statements)
references
References 51 publications
80
1,040
11
74
Order By: Relevance
“…Besides the important emphasis on a number representation (Butterworth, 1999;2005;Noël & Rouselle, 2011), studies focus on executive functioning as well (Bull & Scerif, 2001;D'Amico & Passolunghi, 2009;De Weerdt, Desoete & Roeyers, 2012). Research has shown that inhibition is predictive for mathematical abilities and necessary in math performance for the active suppression of immature or incorrect strategies (Bull & Scerif, 2001).…”
Section: Behavioral Inhibition In Children With Mathematical Disabilimentioning
confidence: 99%
See 3 more Smart Citations
“…Besides the important emphasis on a number representation (Butterworth, 1999;2005;Noël & Rouselle, 2011), studies focus on executive functioning as well (Bull & Scerif, 2001;D'Amico & Passolunghi, 2009;De Weerdt, Desoete & Roeyers, 2012). Research has shown that inhibition is predictive for mathematical abilities and necessary in math performance for the active suppression of immature or incorrect strategies (Bull & Scerif, 2001).…”
Section: Behavioral Inhibition In Children With Mathematical Disabilimentioning
confidence: 99%
“…Research has shown that inhibition is predictive for mathematical abilities and necessary in math performance for the active suppression of immature or incorrect strategies (Bull & Scerif, 2001). Children with MD and -to a lesser extent-control children might for instance have the tendency to make tablerelated or counting-string errors (Geary, 2011).…”
Section: Behavioral Inhibition In Children With Mathematical Disabilimentioning
confidence: 99%
See 2 more Smart Citations
“…Links have been found between these working memory abilities and attainments in the areas of reading (e.g., De Jong, 1998;Swanson, 1994), mathematics (e.g., Bull & Scerif, 2001;Mayringer & Wimmer, 2000;Siegal & Ryan, 1989), and language comprehension (e.g., Nation, Adams, Bowyer-Crane, & Snowling, 1999;Seigneuric, Ehrlich, Oakhill, & Yuill, 2000). Measures of working memory at school entry (at 4 or 5 years, in the UK) have also been found to provide excellent predictors of childrenÕs success in national assessments of scholastic abilities up to 3 years later (Gathercole, Brown, & Pickering, 2003).…”
Section: Introductionmentioning
confidence: 99%